Overcoming Memory T cell Responses for Induction of Delayed Tolerance in Nonhuman Primates - Yamada, Y. (2011)
The presence of alloreactive memory T cells is a major barrier for induction of tolerance in primates. In theory, delaying conditioning for tolerance induction until after organ transplantation could further decrease the efficacy of the regimen, since pre-existing alloreactive memory T cells might be stimulated by the transplanted organ. Here, we show that such “delayed tolerance” can be induced in nonhuman primates through the mixed chimerism approach, if specific modifications to overcome/avoid donor-specific memory T cell responses are provided. These modifications include adequate depletion of CD8+ memory T cells and timing of donor bone marrow administration to minimize levels of pro-inflammatory cytokines. Using this modified approach, mixed chimerism was induced successfully in 11 of 13 recipients of previously placed renal allografts and long-term survival without immunosuppression could be achieved in at least 6 of these 11 animals.